European interdisciplinary guideline on invasive squamous cell carcinoma of the skin: Part 1. epidemiology, diagnostics and prevention. (March 2020) - Stratigos, Alexander J.; Garbe, Claus; Dessinioti, Clio; Lebbe, Celeste; Bataille, Veronique; Bastholt, Lars; Dreno, Brigitte; Fargnoli, Maria Concetta; Forsea, Ana Maria; Frenard, Cecille; Harwood, Catherine Α.; Hauschild, Axel; et al.
Abstract: Invasive cutaneous squamous cell carcinoma (cSCC) is one of the most common cancers in the white populations, accounting for 20% of all cutaneous malignancies. Factors implicated in cSCC etiopathogenesis include ultraviolet radiation exposure and chronic photoaging, age, male sex, immunosuppression, smoking and genetic factors. A collaboration of multidisciplinary experts from the European Dermatology Forum (EDF), the European Association of Dermato-Oncology (EADO) and the European Organisation of Research and Treatment of Cancer (EORTC) was formed to update recommendations on cSCC classification, diagnosis, risk stratification, staging and prevention, based on current literature, staging systems and expert consensus. Common cSCCs are typically indolent tumors, and most have a good prognosis with 5-year cure rates of greater than 90%, and a low rate of metastases (<4%). Further risk stratification into low-risk or high-risk common primary cSCC is recommended based on proposed high-risk factors. Advanced cSCC is classified as locally advanced (lacSCC), and metastatic (mcSCC) including locoregional metastatic or distant metastatic cSCC. Current systems used for staging include the American Joint Committee on Cancer (AJCC) 8th edition, the Union for International Cancer Control (UICC) 8th edition, and Brigham and Women's Hospital (BWH) system. Physical examination for all cSCCs should include total body skin examination and clinical palpation of lymph nodes, especially of the draining basins. Radiologic imaging such as ultrasound of the regional lymph nodes, magnetic resonance imaging (MRI), computed tomography (CT), positron emission tomography–computed tomography (PET-CT) scans are recommended for staging of high-risk cSCC. Sentinel lymph node biopsy is currently not recommended. Nicotinamide, oral retinoids, and topical 5-FU have been used for the chemoprevention of subsequent cSCCs in high-risk patients but are not routinely recommended. Education about sun protection measures including reducing sun exposure, use of protective clothing, regular use of sunscreens and avoidance of artificial tanning, is recommended. Highlights: Clinical diagnosis of cSCC is confirmed by histology. Ιnvasive cSCC is classified as high-risk or low risk for recurrence or metastasis. Risk classification is based on tumour- and patient-related risk characteristics. Staging systems of cSCC are based on TNM classification and require refinement.